Novel Functions of Hendra Virus G N-Glycans and Comparisons to Nipah Virus - Bradel-Tretheway, Birgit G. (J Virol, 2015)
Hendra virus (HeV) and Nipah virus (NiV) are reportedly the most deadly pathogens within the Paramyxoviridae family. These two viruses bind the cellular entry receptors ephrin B2 and/or ephrin B3 via the viral attachment glycoprotein G, and the concerted efforts of G and the viral fusion glycoprotein F result in membrane fusion. Membrane fusion is essential for viral entry into host cells and for cell-cell fusion, a hallmark of the disease pathobiology. HeV G is heavily N-glycosylated, but the functions of the N-glycans remain unknown. We disrupted eight predicted N-glycosylation sites in HeV G by conservative mutations (Asn to Gln) and found that six out of eight sites were actually glycosylated (G2 to G7); one in the stalk (G2) and five in the globular head domain (G3 to G7). We then tested the roles of individual and combined HeV G N-glycan mutants and found functions in the modulation of shielding against neutralizing antibodies, intracellular transport, G-F interactions, cell-cell fusion, and viral entry. Between the highly conserved HeV and NiV G glycoproteins, similar trends in the effects of N-glycans on protein functions were observed, with differences in the levels at which some N-glycan mutants affected such functions. While the N-glycan in the stalk domain (G2) had roles that were highly conserved between HeV and NiV G, individual N-glycans in the head affected the levels of several protein functions differently. Our findings are discussed in the context of their contributions to our understanding of HeV and NiV pathogenesis and immune responses. IMPORTANCE Viral envelope glycoproteins are important for viral pathogenicity and immune evasion. N-glycan shielding is one mechanism by which immune evasion can be achieved. In paramyxoviruses, viral attachment and membrane fusion are governed by the close interaction of the attachment proteins H/HN/G and the fusion protein F. In this study, we show that the attachment glycoprotein G of Hendra virus (HeV), a deadly paramyxovirus, is N-glycosylated at six sites (G2 to G7) and that most of these sites have important roles in viral entry, cell-cell fusion, G-F interactions, G oligomerization, and immune evasion. Overall, we found that the N-glycan in the stalk domain (G2) had roles that were very conserved between HeV G and the closely related Nipah virus G, whereas individual N-glycans in the head quantitatively modulated several protein functions differently between the two viruses.